SLOVENES TO EUROPE WITH BUREK AND /OR THE DICTATORSHIP OF KRANJSKA KLOBASA: SOMETHING ABOUT BUREK, REPRESENTATIONS OF BUREK, AND “SLOVENE” ETHNO-NATIONAL DISCOURSE - Mlekuž, Jernej (Two Homelands, 2006)
Burek – a pie of various fillings “came” to Slovenia with immigrants from the republics of former Yugoslavia. In the beginning, it was confined to the family kitchen of immigrants; in the 80s, it emerged mainly in urban environment in the choice of some fast-food shops. At first, the consumption was linked above all to the immigrants. Later, part of the young population in urban environments began consuming burek. The end of the 60s and the entire 90s present a period when burek was gaining emphasised political meanings that were mainly linked to ethnic-national discourse. The mentioned period was also the time of expansion of this alimentary product, when not only its production and consumption increased (some Slovene bakeries and shops began preparing and selling burek), but it also left a noticeable seal in popular culture, in media, graffiti, slang etc. The contribution presents the relation between a chosen alimentary object with emphasised immigrant “outlandish” connotation and the (Slovene) ethno-national discourse. It analyses above all different representations of burek in journalistic texts, semi-textual graffiti texts, names and other; occasionally it peeks into other processes as well in which meanings are being formed (production, regulation, consumption and other). The contribution reveals two discourses regarding burek, the nationalistic and the anti-nationalistic. In the so-called nationalistic discourse, burek is being associated with negative connotations and meanings; it becomes an indicator of the “inferior culture of the South”. Parallel with this discourse, possibly with partial time delay, alternative political meanings of burek occur. Those were usually not formulated as explicit revolt against nationalism but on the level of meanings, they were more or less in discordance with the nationalist discourse. Especially among younger urban population, students and schoolchildren, burek began increasingly functioning as a sign of something “cool” and thus brought about other meanings of “Juga” and “Balkan”. The contribution also presents the relation of representations to other processes in which meaning are being created. Namely, the creation of a meaning does not occur within practices, ways of representation only but as well within processes of production, consumption, regulation, and in regard of type of identities linked to the object (de Guy et al. 2000). Cultural meanings of burek thus derive from practices of production, distribution and application and with that connected identities: the fact that burek is primarily being prepared in the kitchens of immigrants and that mainly Albanians, that is immigrants, foreigners, bake and sell it on the streets, seems to be the “output base” of production of meanings of burek in Slovenia, at least in the context of ethno-national discourse. Not negligible on the level of meanings is the fact that “Slovene” bakeries began baking it and “Slovene” shops selling it. Numerous meanings of burek have emerged and still are, through processes of consumption. We could set a thesis that at least part of the youth in the 90s used the consumption of burek as indicators in the active process of constructing “opposition” identities. However, those are issues for the next “burek story”.